Synthesis and Anti-Bacterial Activity Test of Chalcone Analogue Compounds From 1-Acetylnaphthalene With Furfural - Maryanti, Desti Ayu; Fitria, Dori; Putri, Riski Dwimalida (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2025)
Abstract: The development of antibacterials has become crucial due to the emergence of antibiotic-resistant bacteria. One such antibacterial is a chalcone analogue compound, known to possess various biological activities useful in medicine. This study aims to synthesize a compound of chalcone analogues and test for anti-bacterial activity. Chalcone analogue compounds from 1-acetylnaphthalene with furfural in this study have been successfully synthesized using a cross aldol condensation reaction with the stirrer method. The structure obtained is a chalcone analogue compound with a synthesis yield of 97%, and the target structure was confirmed by FTIR and NMR instruments. In this study, chalcone analogue compounds have anti-bacterial activity against Escherichia coli and Staphylococcus aureus bacteria with the agar diffusion testing method. Results of the antibacterial test in this study showed a moderate analogue category for S. aureus bacteria and weak for E. coli bacteria. This is evidenced by the concentration of 40 mg/mL having an inhibition zone for S. aureus bacteria of 9.5 mm and E. coli bacteria of 0.5 mm. Chalcone compounds can be intermediate compounds that can be resynthesized with other compounds and have various biological activities. So, this study can be used as a reference for literacy to develop the theory of synthesis of chalcone analogue compounds as new drug candidates. Abstrak: Pengembangan antibakteri menjadi penting seiring dengan adanya bakteri yang resisten terhadap antibiotik. Salah satu antibakteri tersebut adalah senyawa analog kalkon yang dikenal memiliki berbagai aktivitas biologis yang berguna dalam pengobatan. Penelitian ini bertujuan untuk mensintesis senyawa analog kalkon dan menguji aktivitas antibakterinya. Senyawa analog kalkon dari 1-asetilnaftalena dengan furfural dalam penelitian ini telah berhasil disintesis menggunakan reaksi kondensasi aldol silang dengan metode pengadukan. Struktur yang diperoleh adalah senyawa analog kalkon dengan rendemen sebesar 97% dan struktur target dikonfirmasi oleh instrumen FTIR dan NMR. Dalam penelitian ini, senyawa analog kalkon memiliki aktivitas antibakteri terhadap bakteri Escherichia Coli dan Staphylococcus Aureus dengan metode pengujian difusi agar. Hasil uji antibakteri dalam penelitian ini menunjukkan kategori sedang untuk bakteri S. aureus dan lemah untuk bakteri E. coli. Hal ini dibuktikan dengan konsentrasi 40 mg/mL yang memiliki zona inhibisi untuk bakteri S. aureus sebesar 9,5 mm dan bakteri E. coli sebesar 0,5 mm. Senyawa kalkon dapat menjadi senyawa perantara yang dapat disintesis ulang dengan senyawa lain dan memiliki berbagai aktivitas biologis. Oleh karena itu, penelitian ini dapat digunakan sebagai referensi untuk pengembangan teori sintesis senyawa analog kalkon sebagai kandidat obat baru.